Creative Thinking Skill in Solving Mathematics Story Questions for Eight Graders (Universitas Negeri Semarang, 2022)
Mathematics creative thinking skills of learners are still low Mathematics learners could not solve mathematics story questions in non-routine manner The success of mathematics learning is based on the capability of learners to remember and apply the given steps, rules, and examples from the teachers These low performances make learners less creative to solve mathematics story questions This research aims to (1) analyze the mathematics creative thinking skill in solving mathematics story questions for learners taught by CPS and learners taught by discovery learning, and (2) describe the mathematics creative thinking skills in solving the questions The researchers used a test to collect the data The results showed that (1) the mathematics creative thinking skills of learners in solving story questions for learners with CPS were better than those taught by discovery learning Secondly, the learners with mathematics creative thinking skills could solve high-level mathematics story questions based on creative thinking indicators and four-stage solution On the other hand, learners with moderate mathematics creative thinking skills could solve questions with an indicator of creative thinking However, they could not solve the questions with four-stage solution Learners with low-level mathematics creative thinking skills could not solve the questions with the indicator of creative thinking skills The research results are useful to enrich knowledge about mathematics creative thinking skill development in solving mathematics story questions with the CPS model.